2017
DOI: 10.1017/s0033291717002215
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of suicidal thoughts and behaviours among college students: a meta-analysis

Abstract: Based on the currently available evidence, STB seem to be common among college students. Future studies should: (1) incorporate refusal conversion strategies to obtain adequate response rates, and (2) use more fine-grained measures to assess suicidal ideation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
225
10
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 354 publications
(273 citation statements)
references
References 79 publications
17
225
10
6
Order By: Relevance
“…In countries with marked differences in culture, language, and level of socioeconomic development, lifetime prevalence of STB among college entrants is 7.2%, and 12-month prevalence of STB in college is 1.9%. Surprisingly, these prevalence rates are three to six times lower than the lifetime and 12-month prevalence in a recent meta-analysis of 36 college student probability samples worldwide [3]. Methodological issues may explain these conflicting results.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…In countries with marked differences in culture, language, and level of socioeconomic development, lifetime prevalence of STB among college entrants is 7.2%, and 12-month prevalence of STB in college is 1.9%. Surprisingly, these prevalence rates are three to six times lower than the lifetime and 12-month prevalence in a recent meta-analysis of 36 college student probability samples worldwide [3]. Methodological issues may explain these conflicting results.…”
Section: Discussionmentioning
confidence: 95%
“…Second, the majority of studies on this topic rely on single-item STB assessments, which often lead to false-positive STB cases [9]; yet, the current study utilized a well-validated clinical interview to assess STB. Third, the majority of previous studies come from the United States [3], where STB prevalence has found to be high [10], whereas the current study presents a well-balanced sample of college students worldwide.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations